APLIKASI ANALISIS SHIFT SHARE ESTEBAN-MARQUILLAS PADA SEKTOR PERTANIAN DI KABUPATEN BOYOLALI - ROPINGI - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
In OTDA era, data and information about allocation effect is very important, becouse its becamecompetitive advantage in this region. The other opportunity is investor pulled with this region. Thisresearch was done in Boyolali Regency. Assessing data from BPS Central Java., Boyolali RegencyThe data and information used in this research was data Gross Regional Domestic Product (GRDP)from 1998 to 2002.. Type of data is secundary. For analysing this research used Esteban-Marquillas Shift Share Analysis (Dinamic SSA/ E-M SSA). The result of this research is (i)Agriculture, Financing, Ownership and Bussiness Services included sectors have competitiveadvantage, specialized (Code 4). (ii)Electricity, Gas, Water Supply, Contruction and Servicesincluded sectors have competitive advantage, not specialized (Code 3). (iii) Mining and Quarrying,Industies included sectors have competitive disadvantage, not specialized (Code 2) (iv) Trade,Hotel, Restaurant, Transport and Comunication included sectors have competitive disadvantage, notspecialized (Code 1). (v) Agricultural sector what it has competitive advantage, specialized (Code 4)are foodstuff plants, and plantation plants. It has competitive advantage, not specialized areforesting and fishing, whereas cattle sector included sector has competitive disadvantage, notspecialized (code 1) (vi) The contribution of Agricultural Sector periode 1998 to 2002 in theeconomy Boyolali regency if seen income multiplier, it trend rise except in 2001, it contributiondecreased.